First aid at the scene in the opinion of the members of Warsaw medical rescue teams - Binkowska, Aneta; Kamecki, Artur (Polish Journal of Public Health, 2017)
Introduction. The ability to provide first aid should be one of the basic skills of each of us. Aim. The aim of the study was to learn the opinion of the members of Medical Rescue Teams (MRT) of the “Meditrans” Provincial Ambulance and Sanitary Transport Service (PA and STS “Meditrans”) in Warsaw on how people react in real situations threatening life or health of the injured person. Material and methods. The study was conducted in the third quarter of 2015 on 335 members of medical rescue teams, including 77 women and 258 men, who provided medical services in the “Meditrans” Provincial Ambulance and Sanitary Transport Service MRT in Warsaw. The research tool was an anonymous questionnaire survey of own design, which consisted of 12 questions: closed, half open and one open question. Results. The majority of respondents have encountered instances of first aid provision, but respondents assessed the frequency of such situations as low. Among the largest group of witnesses providing first aid there are the elderly and youth, who are subjected to various forms of education related to first aid provision. Conclusions. Only continuous education and in particular, practical trainings will help people to overcome the barrier of their limitations in order to help others.